Knowledge, Interest and Perception of Academic Physiotherapists with Regard to Professional Ethics (Medical Forum Monthly, 2021)
Objective: To determine the level of interest, perception and knowledge of professional ethics among physiotherapy academic faculty.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Physical Therapy, University Institute of Physical Therapy, University of Lahore from January 2021 to April 2021.Materials and Methods: Non-probability convenient sampling technique was used to collect data from 104 Physiotherapy academic faculty members. Standardized and modified, self-administered questionnaire was used and collected data were analyzed in SPSS 21.0 for its analysis.Results: The mean age of the academic faculty members was 27.7±3.74 years in which majority (73.1%) were females. About 42.3% faculty had excellent knowledge, 86.5% of the physiotherapists showed medium level of interest towards professional code of ethics. Among all the physiotherapy faculty, 48.1% faculty perceived that code of ethics of physiotherapy must be the part of syllabus in all years of under-graduation (BSPT/tDPT/DPT).Conclusion: Significantly higher level of knowledge and good interest is found in this study with perception of adding code of ethics in syllabus of students for all years and even better to punish the students in case they don't follow the ethical conduct during their academic activities